HEPATOPROTECTIVE EFFECT OF PRAZOSIN IS COMPARABLE TO N-ACETYLCYSTEINE IN ACETAMINOPHEN INDUCED HEPATOTOXICITY IN MICE - Sulaiman, Samra; Hussain, Mazhar; Shad, Muhammad Nauman; Chiragh, Sadia (Journal of Ayub Medical College Abbottabad, 2020)
Background: Autonomic nervous system modulates acetaminophen induced hepatotoxicity. The purpose of the study was to determine the hepatoprotective effect of Î±1 antagonist (prazosin) and Î²2 agonist (salbutamol) on acetaminophen induced hepatotoxicity in mice. Methods: This experimental study was conducted at Post Graduate Medical Institute, Lahore in which 50 adult mice were divided in to five groups. With the exception of normal control, hepatotoxicity was induced in all other study groups by giving single intraperitoneal injection of acetaminophen 300 mg/ kg. First and second groups served as normal and toxic control were given distilled water 6 ml/ kg while third, fourth and fifth experimental groups were given N-acetylcysteine (300 mg/ kg), prazosin (0.18 mg/ kg) and salbutamol (0.35 mg/ kg) intraperitoneally at 2,4 and 8 hours after acetaminophen injection. Serum liver enzymes were analysed at 0 and 72 hours while histopathological finding were assessed at the end of study by using SPSS-20. Results: All the groups treated with toxic dose of acetaminophen showed significant increase in serum ALT, i.e., B (Toxic control 3372%), C (NAC treated 282%), D (Prazosin treated 582%), E(Salbutamol treated 3297%) and AST levels, i.e., B (Toxic control 2750% ), C (NAC treated 230% ), D (Prazosin treated 280%), E(Salbutamol treated 828%) with p-value Ë‚0.001 . When this increase was compared between groups, the lowest increase in serum ALT and AST levels was observed in N-acetylcysteine and prazosin group with no significant difference. Similarly, experimental animals receiving prazosin and N-acetylcysteine had the lowest inflammation, degeneration and necrosis scores than the toxic control group in histopathological analysis of the liver with p-valueË‚0.001. Conclusion: The hepatoprotective effect of prazosin is comparable to N- acetylcysteine against acetaminophen induced hepatotoxicity in mice. Keywords: Hepatotoxicity; Acetaminophen; Prazosin; Salbutamol